Kurikulum Merdeka Dalam Pembelajaran Matematika: Refleksi Kritis terhadap Wacana dan Praktik Pendidikan - Elsha Riyani Saragih; Ayu Majulestari Tampubolon; Yeyen Julfriyana Sitorus; Jatenra Holan Jaya Hutahaean; Putri Julfriyana Purba; Christa Voni Roulina Sinaga (Yayasan Salam Cerdas Al-Fattah, 2025)
This study aims to critically analyze the implementation of the Kurikulum Merdeka (Independent Curriculum) in mathematics education, focusing on the alignment between policy discourse and classroom practices. Utilizing a literature review approach, this research examines relevant national and international sources and synthesizes findings related to the challenges, innovations, and reflective practices surrounding the curriculum implementation. The analysis reveals that although the Kurikulum Merdeka promotes flexible, contextual, and student-centered learning, its practical application still encounters pedagogical, cultural, and structural barriers. Innovations such as project-based learning, ethnomathematics integration, and digital media utilization offer promising strategies, yet these remain hindered by insufficient teacher readiness and systemic support. This study recommends strengthening teachers’ professional capacities, transforming school learning cultures, and conducting further practice-based research to authentically embed the spirit of independent learning into mathematics instruction in a sustainable manner.